Utilizing verification and validation certificates to estimate software defect density. - Sherriff, Mark
In industry, information on defect density of a product tends to become available too late in the software development process to affordably guide corrective actions. Our research objective is to build a parametric model which utilizes a persistent record of the validation and verification (V&V) practices used with a program to estimate the defect density of that program. The persistent record of the V&V practices are recorded as certificates which are automatically recorded and maintained with the code.PhD Advisor: Dr. Laurie Williams, williams@csc.ncsu.edu
Keywords: Software; Software engineering; Metrics; Performance measures; Process metrics; Product metrics; Design; Measurement; Reliability; Reliability estimation; Software reliability engineering; Validation and verification management